SEALIVE: the use of technical vessel-sealing devices for recipient hepatectomy in liver transplantation : study protocol for a randomized controlled trial - Houben, Philipp; Khajeh, Elias; Hinz, Ulf; Knebel, Phillip; Diener, Markus K.; Mehrabi, Arianeb (Trials, 2018)
The surgical technique used in liver transplantation has undergone constant evolution in an effort to develop a safe, highly standardized procedure. Despite this, the initial step of recipient hepatectomy has not been the focus of clinical research thus far. Due to advanced coagulopathy in liver transplant recipients, this part of the operation still carries the risk of severe hemorrhage. This trial is designed to compare an electrothermal bipolar vessel sealing device (LigaSure™) and an ultrasound dissector (HARMONIC ACE®+7) with standard surgical techniques during the recipients’ hepatectomy in liver transplantation.